2012
DOI: 10.1111/j.1551-6709.2012.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Novelty in Early Word Learning

Abstract: What mechanism implements the mutual exclusivity bias to map novel labels to objects without names? Prominent theoretical accounts of mutual exclusivity (e.g., Markman, 1989Markman, , 1990 propose that infants are guided by their knowledge of object names. However, the mutual exclusivity constraint could be implemented via monitoring of object novelty (see Merriman, Marazita, & Jarvis, 1995). We sought to discriminate between these contrasting explanations across two preferential looking experiments with 22-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 48 publications
7
80
2
Order By: Relevance
“…Each child was presented with nine sets and saw each set once on a known name trial and once on a novel name trial for a total of 18 referent selection trials. Known name referent selection trials were included as a control to ensure that children were mapping the names to the targets and not simply mapping novelty to novelty (see also Horst, Samuelson, Kucker, & McMurray, ; Mather & Plunkett, ). Each set included two familiar objects (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Each child was presented with nine sets and saw each set once on a known name trial and once on a novel name trial for a total of 18 referent selection trials. Known name referent selection trials were included as a control to ensure that children were mapping the names to the targets and not simply mapping novelty to novelty (see also Horst, Samuelson, Kucker, & McMurray, ; Mather & Plunkett, ). Each set included two familiar objects (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research demonstrates that children have a endogenous bias to novelty (Horst et al, 2011b). Specifically, when presented with a novel word and no supportive information about the target referent (i.e., without known competitors), rather than responding randomly, children systematically link the novel word to the most novel object (see also, Mather and Plunkett, 2012). Importantly, this bias can be seen after as little as 2 min of exposure with previously novel objects.…”
Section: Considerations For Word Learning and Storybook Researchmentioning
confidence: 99%
“…In most cases, children had to pick out the correct referent from an array of objects that included the newly learned referent and several familiar referents. Recent studies have demonstrated that the saliency of novel objects significantly influences young children’s choices in comprehension tasks (Mather and Plunkett, 2012). When novelty is controlled for (by including foils that are equally as novel as the trained word), 2-year-olds do not show comprehension of newly mapped word after a 5-min delay in a pointing task (Horst and Samuelson, 2008; see also Kucker and Samuelson, 2011).…”
Section: What We Know About Retention and Word Learningmentioning
confidence: 99%